IMPLEMENTASI PERATURAN DAERAH NOMOR 03 TAHUN 2012 MENGENAI TEMPAT PEMAKAMAN UMUM DI KOTA PEKANBARU TAHUN 2014 - Surya Fernando; Muhammad Ridwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Indonesia embraced decentralization system in accordance with Law No. 32 of 2004 , in which the central government delegate / give up some power and authority to local governments to regulate and manage part of the authority and the power of the Unitary State of the Republic of Indonesia . One policy area in the city of Pekanbaru , issued a policy in the form of Regional Regulation No. 03 Year 2012 on Levy Funeral Service , incineration corpse . Burial in Pekanbaru itself pretty much covers have public , private and governmental . Remains of the many burial spread across 12 districts Pekanbaru , which is managed by the government is only six , but who has the appropriate regulations only two . Based on the description above, the authors are interested in doing research with the title "Implementation of Regional Regulation No. 03 of 2012 Concerning the General Cemetery in the city of Pekanbaru 2014A fundamental problem in this research that there are many common burial sites managed by the Department of Social and Pekanbaru City Cemetery is not in accordance of the contents of local regulation number 03 of 2012 chapter eight , then the factors inhibiting the implementation of these local regulations , both internally and externally . Theory ( approach ) that I use as an analytical tool in this research is the theory of Policy Implementation . While research method used in this study is a qualitative research , which seeks to analyze the implementation and obstacles derived from observations and aim to reinforce and strengthen the theory so as to obtain information on the current situation. Data collection techniques in this study is to interview techniques and documentation.We can conclude this study , the implementation of local regulation number 03 of 2012 in the city of Pekanbaru is still far from expectations . Still more than half the burial place of the common run local governments is not the appropriate local regulations . The cause and the inhibiting factor among others because of communication problems , the means and the estimated time funeralKeywords : Implementation, Regional Regulation, General Cemetery